2009
DOI: 10.1007/s10562-009-9913-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of In situ/Ex situ Activated Trimetallic NiMoW Sulfide Catalysts Prepared from Ammonium Thiomolybdotungstates

Abstract: Unsupported trimetallic NiMoW sulfide catalysts with high hydro-desulphurization activities are prepared from Ni-containing ammonium thiomolybdo tungstates by in situ and ex situ activation. These precursors are prepared by adding an aqueous NiCl 2 solution to an aqueous (NH 4 ) 4 MoWS 8 solution in either a 1:1 or 0.5:1 Ni/Mo(W) molar ratio. The resulting precursors Ni 0.5 / (NH 4 ) 4 MoWS 8 and Ni/(NH 4 ) 4 MoWS 8 yield Ni 0.5 MoW-in situ, NiMoW-in situ, Ni 0.5 MoW-ex situ and NiMoW-ex situ sulphide catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Besides pore dispersing action, it contributes to the wetting and plasticizing functions [16][17][18][19][20][21][22][23]. Research has shown that the introduction of additives during the preparation of the catalyst increases its activity in hydrodesulfurization and denitrification reactions [24].…”
Section: Additivementioning
confidence: 99%
“…Besides pore dispersing action, it contributes to the wetting and plasticizing functions [16][17][18][19][20][21][22][23]. Research has shown that the introduction of additives during the preparation of the catalyst increases its activity in hydrodesulfurization and denitrification reactions [24].…”
Section: Additivementioning
confidence: 99%
“…As consequence, Soled et al [9] synthesized and patented the first unsupported NiMoW trimetallic catalyst, called NEBULA, which may be more effective than the conventional one used in industry. Nowadays the potential of applying NiMoW catalysts for HDT has been explored [10][11][12][13] and it has been reported that when Mo is partially substituted by W, an amorphous phase is created, which after reduction and sulphidation produces catalytically active materials. Despite the high catalytic activity for the unsupported NiMoW catalysts, they have the disadvantage of high cost and low utilization of active components, therefore further research is still required [14].…”
Section: Introductionmentioning
confidence: 99%
“…Ammonium thiometallates have already been extensively studied as potential precursors for HDS catalysts [4][5][6][8][9][10] Electronic supplementary material The online version of this article (doi:10.1007/s10562-009-0209-3) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%